Quality Assurance of Academic Organisations – A Comparative Study of ISO 9001, ISO 21001 and QAA (UGC Nepal) - Timsina, Tatwa P (Journal of Advanced Academic Research, 2022)
With the establishment of the first school in 1853, the era of modern education began in Nepal. Though it was aimed only for the members of the ruling families and their courtiers, it attracted the interest of the ordinary people as well. After about 100 years later, schooling for the general people began in 1951 after the over throw of autocratic regime. Even after these seven decades of educational history, the quality of education system in Nepal is still poor. After the introduction of the private education system, the gap between poor and rich in terms of education has widened. Like in many countries, School Education in Nepal comprises Primary Level, Middle School/Lower Secondary Level (SLC), High School/ Secondary Level and +2/ Higher Secondary Level. Bachelor's/Undergraduate Level, Master's Level/Graduate/Degree Level, Post Graduate, MPhil Level and PhD Doctoral Level are the part of Higher Education system.